2016
DOI: 10.1186/s12889-016-3622-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and school dropout across educational levels and genders: a 4.8-year follow-up study

Abstract: BackgroundEducation is a key determinant of future employment and income prospects of young people. Poor mental health is common among young people and is related to risk of dropping out of school (dropout). Educational level and gender might play a role in the association, which remains to be studied.MethodsMental health was measured in 3146 Danish inhabitants aged 16–29 years using the 12-Item Short-Form Health Survey and examined across genders and educational levels. For students, educational level at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 48 publications
6
113
1
7
Order By: Relevance
“…In literature economic level is informed as one of the factors which affects dropouts (Hjorth et al, 2016;RowanKenyon, 2007;Ruban, Petersen, & Møller-Madsen, 2013) which is supported with the findings of the presented study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In literature economic level is informed as one of the factors which affects dropouts (Hjorth et al, 2016;RowanKenyon, 2007;Ruban, Petersen, & Møller-Madsen, 2013) which is supported with the findings of the presented study.…”
Section: Discussionsupporting
confidence: 75%
“…In literature first year of college was associated with high levels of stress since it is an adaptation period to new conditions (Chaló, Pereira, Batista, & Sancho, 2017;Dyson & Renk, 2006) and also associated with high rate of school dropouts (Hjorth et al, 2016), freshmen period seems as an especially important period. Therefore freshmen and seniors were included as participants of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health problems such as suicide ideation, severe substance use, depression and anxiety have been associated to academic performance [5][6][7][8] and dropping out of higher education. 9 However, a few studies have found no such associations. 10,11 Thus, incoming first-year students with a prior untreated psychopathology, which may be exacerbated by new demands, may have a more difficult transition to university, affecting their academic achievement and ultimately their chances of graduation.…”
mentioning
confidence: 99%